CPO Product Quality Control at PT. Kurnia Mitra Sawit Using The T2 Hotelling Method - Panjaitan, Rio Anggara (UIN Sumatera Utara Medan, 2025)
This study aims to analyze the stability of the Crude Palm Oil (CPO) production process at PT. Kurnia Mitra Sawit through a multivariate quality control approach using the T² Hotelling method. The background of this study is based on the importance of maintaining CPO quality in accordance with company standards, especially for key quality parameters such as Free Fatty Acid (FFA), moisture content, and dirt content. Uncontrolled parameters can reduce product quality and affect the selling price of CPO in the market. The research was conducted by collecting production data and performing statistical tests using the T² Hotelling diagram to detect simultaneous process variations. Initial analysis results showed that several samples were outside the upper control limit (UCL), indicating specific causes in the production process. However, after repeated improvements and controls, all data points were finally within the control limits, with a UCL value of 18.68 and a median of 3.70. This indicates that the production process is statistically controlled and contains only natural variation. Thus, this method is effective for monitoring the stability of the CPO production process and preventing quality deviations in the future.